PEDAGOGICAL STRATEGIES FOR IDENTIFYING DYSLEXIA: ON THE EXAMPLE OF ASIA AND LATIN AMERICA - Khamraeva Khullar Naimovna (TADQIQOTLAR, 2025)
Annotation: Attention is drawn to the significant differences in diagnostic criteria and procedures depending on the linguistic characteristics of the language, educational systems and cultural context. A comparative analysis of diagnostic methods used in Asia and Latin America is conducted, common aspects and significant differences are identified. The article emphasizes the need to take into account sociocultural factors and calls for international exchange of experience to improve the identification and support of individuals with dyslexia worldwide.